INKULTURASI IMAN: DINAMIKA BUDAYA DAN TEOLOGI PENTAKOSTA DALAM KONTEKS MODERN - Pasaribu, George Rudi Hartono (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2025)
This article examines the relationship between Pentecostal theology and local culture in the context of faith inculturation, with the aim of understanding the challenges faced by Pentecostal churches in reaching culturally diverse communities. The research employs a qualitative method with a literature review approach, analyzing theological literature, the Bible, academic journals, and relevant articles. The discussion focuses on how Pentecostal churches can integrate the teachings of the Gospel with local culture without compromising theological essence, considering obstacles such as cultural dualism, fear of syncretism, and the lack of cultural understanding among church leaders. The author also explores the example of Jesus in interacting with culture, emphasizing that culture can be used to convey the divine message without undermining the essence of God's word. In conclusion, faith inculturation in Pentecostal theology allows the church to remain relevant to the local cultural context through appreciation of local traditions that do not contradict Christian teachings, while maintaining fidelity to the Bible and the guidance of the Holy Spirit.